The Effect of Emotion on Prosocial Tendency: The Moderating Effect of Epidemic Severity Under the Outbreak of COVID-19 - Ye, Yingying; Long, Tingting; Liu, Cuizhen; Xu, Dan (Frontiers in Psychology, 2020)
During the outbreak of COVID-19, information on the epidemic inundated people’s lives and led to negative emotions (e.g., tension, anxiety, and fear) in many people. This study aims to explore the effect of various emotions on prosocial tendencies during the COVID-19 outbreak and the moderating effect of the severity of the epidemic. We explore these effects by conducting a text analysis of the content of posts by 387,730 Weibo users. The results show that the severity of the epidemic promotes prosocial tendencies; anger motivates prosocial tendencies significantly; and the severity of the epidemic moderates the effects of three emotions—anger, sadness, and surprise—on prosocial tendencies. These findings provide a reference for exploring the positive significance of major disasters.